2009
DOI: 10.1002/anie.200806265
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle Formation in Different Sizes Induced by Peptides Identified within Split‐and‐Mix Libraries

Abstract: Silver nanoparticles (AgNPs) are becoming increasingly important for manifold applications in, for example, imaging, catalysis, electronics, and the development of antimicrobial coatings. [1][2][3] The formation of AgNPs is typically accomplished by chemical reduction or irradiation of Ag + ions with visible light in the presence of additives, such as polymers or surfactants, which induce the formation of AgNPs and stabilize the NPs. [1,2] Recently, peptides bearing functional groups that coordinate to Ag + io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 46 publications
1
48
0
1
Order By: Relevance
“…122 Also, Adhikari and Banerjee 123 reported that in a short peptide-based hydrogel, the light-induced formation of silver nanowires is possible due to the combination of a carboxylic acid-containing peptide (Fmoc-Val-Asp-OH) and sunlight. 123 These observations are in agreement with the results reported by Belser et al 118 who showed that a tetrapeptide containing Asp and Ser linked by a rigid linker that does not spontaneously form AgNPs upon incubation with silver nitrate is able to mineralize silver only in the presence of light. The suggested influence of the complexation with a peptide on the redox potential of silver is discussed controversially since the work of Carter et al 124 showed that the silver redox potential does not change in the presence of a glutamate hexamer.…”
Section: Peptides For the Formation Of Silver Nanostructuressupporting
confidence: 91%
See 1 more Smart Citation
“…122 Also, Adhikari and Banerjee 123 reported that in a short peptide-based hydrogel, the light-induced formation of silver nanowires is possible due to the combination of a carboxylic acid-containing peptide (Fmoc-Val-Asp-OH) and sunlight. 123 These observations are in agreement with the results reported by Belser et al 118 who showed that a tetrapeptide containing Asp and Ser linked by a rigid linker that does not spontaneously form AgNPs upon incubation with silver nitrate is able to mineralize silver only in the presence of light. The suggested influence of the complexation with a peptide on the redox potential of silver is discussed controversially since the work of Carter et al 124 showed that the silver redox potential does not change in the presence of a glutamate hexamer.…”
Section: Peptides For the Formation Of Silver Nanostructuressupporting
confidence: 91%
“…Interestingly, these results imply that cysteine is a better ligand for Ag(I) than lysine, which is not in agreement with the calculated binding affinities discussed previously in section 2.1.1 (see Table 1). A similar system was investigated by Belser et al 118 who observed that a tripeptide containing both tyrosine and histidine as a strong silver binder is able to mineralize silver only after irradiation. The above summarized results for the involvement of tyrosine in the reduction process of silver clearly indicate that there is still a long way to go to understand the mechanistic pathways involved in the mineralization of silver, and it has to be seen whether the formation of dityrosine takes place in response to the presence of silver ions.…”
Section: Peptides For the Formation Of Silver Nanostructuresmentioning
confidence: 88%
“…In our hands, we focus on several applications in the context of silver chemistry on one hand and the ligand Lin on the other. One is concerned with the generation of silver nanoparticles [19,20], as we were able to show that our compounds possess good light stability in the cases where the silver ions are spaced from each other [15,7], or poor light stability if silver ions are arranged close to each other [7]. Another application deals with the antimicrobial properties of the silver ions, for which we were able to show that compounds e.g.…”
Section: Applications and Outlooksmentioning
confidence: 79%
“…[36,37] Furthermore, the ligand has to be easily synthesized and available in large quantities at a low cost, because it rently in development as coatings for implant materials. [44][45][46][47] With the longer ligand L2, mainly metallacycles based on two silver ions and two ligands are observed, with the exception of a one-dimensional simple helical compound (Fig. 4) [48] and a two-dimensional polycatenated structure.…”
Section: Transition Metal Coordination Compounds and Polymersmentioning
confidence: 99%